Analysis of PARP inhibitor toxicity by multidimensional fluorescence microscopy reveals mechanisms of sensitivity and resistance - Jone Michelena (Nature Portfolio, 2018)
Methods to study anti-cancer drugs cytotoxicity are often low throughput and rely on population average. Here the authors present an automated image-based cytometry method to quantify multiple cytotoxicity parameters in single cells, and use it to study the effect of PARP inhibitors in cancer cells.